VARIATION OF MORPHOMETRIC CHARACTERS AND MARKING PATTERN AMONG THE INDONESIAN POPULATIONS OF THE LESSER BANDED HORNET, Vespa affinis (HYMENOPTERA: VESPIDAE) BASED ON THE SPECIMENS IN THE COLLECTION OF MUSEUM ZOOLOGICUM BOGORIENSE (MZB) - Diah Pusparina; I Wayan Suana; Raden Pramesa Narakusumo; Hari Nugroho (BRIN Publishing (Penerbit BRIN), 2024)
Vespa affinis is a hornet with wide geographical distribution, occurring across the Indonesian Archipelago (Sumatra, Java, Kalimantan, Sulawesi, the Moluccas, and Papua) but excluding the Lesser Sunda Islands. Species with wide distribution typically show morphological variations that may differ across their range. This study aims to provide a detailed description of island-to-island diversity in morphometric characters and marking patterns among Indonesian populations of V. affinis. A total of 18 morphometric characters and 18 color patterns were analyzed. Principal Component Analysis (PCA) and Linear Discriminant Analysis (LDA) were employed to distinguish variations in morphometric data. Marking pattern data were analyzed using the hierarchical clustering, to understand the clustering and relationship of marking patterns. The morphometric similarity recorded across the Indonesian archipelago suggests limited morphometric divergence among the populations. The marking patterns of V. affinis showed considerable variation across its geographical range, with brighter coloration in populations from eastern Indonesia compared to those from Sundaland.